(untitled) (Journal of the Bangladesh Agricultural University, 2014)
Rice (Oryza sativa L.) is the most important food crop of the developing world and the staple food of more than half the global population. An experiment was carried out to identify the iron rich rice genotypes. Total fifty two rice genotypes were used for this purpose. Iron (Fe) content of rice grain samples was determined by using Atomic Absorption Spectrophotometer (AAS). In this process the samples were digested by the application of di-acid mixture which includes nitric acid (HNO3): and perchloric acid (HClO4) in 2:1 ratio. Iron content was estimated in the aliquot of seed extract by using Atomic Absorption Spectrophotometer (AAS) at 248.33 nm. Iron concentration ranged from 1.32 ppm (Jota Balam) to 100.45 ppm (Lal Gotal). Among the 52 genotypes local landraces had showed the highest Fe content. In this experiment, ANOVA table revealed that significant variation was found among the genotypes for the iron concentration. This suggested that there were inherent genetic differences among the genotypes. Thus, local landraces can be a good source for biofortification of popular rice cultivars using different breeding methods. DOI: http://dx.doi.org/10.3329/jbau.v11i1.18216 J. Bangladesh Agril. Univ. 11(1): 73-78, 2013